MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN PERAN AKTIF SISWA BELAJAR MATA PELAJARAN SISTEM REM - Subur Riyono; Samsul Hadi (Universitas Sarjanawiyata Tamansiswa, 2016)
The Implementation of Numbered Head Together (NHT) learning model to Enhance the students Active Role in Learning the Brake System. A thesis of Machine Engginering Education Study Program Faculty of Teacher Training and Educatioon of Sarjanawiyata Tamansiswa University Yogyakarta, 2016.The type of this research is action research including three cycles. Each cycle is conducted by four stages including 1. Planning 2. Implementing 3. Observing and 4. Reflexting. In collecting the Data, the researcher appied test, observation as well as document. The technique used in analyzing the observation sheet and test is quantitive deskriptive.Â The result of this research showed that the implementation of Numbered Head Together (NHT) learning model had enhanched both the students learning Active Role and the studentsâ€™ learning results of the brake system subject to each cycle. It is proved by the increasing result of the observation sheet of the students learning Active Role from which the first cycle 44,57% having increased to the second cycle 16,57% becoming 61,14% and in the third cycle having increased 25,57% becoming 86,71%. Furthermore, based on the learning result testÂ of the first cycle gave the average grade of the pre test 62,28%, the average grade of the post test then 60,71%, the average grade 69,57% so the learning result increased 8,86% and in the second cycle gave the average grade of pretest 62,28% and the average post test then 75,42% increased the learning result 13,14% and the the test of the third cycle, the average pre test 65,14% and the average post test 83,42%.. Due to the research findings, it can be concluded that the implementation of the Numbered Head Together (NHT) learning model can enhance the students learning Active Role as well as the results of the students learning in the brake system.